TERAPI 2-ADRENERGIK KERJA PANJANG PADA TATALAKSANA PENYAKIT PARU OBSTRUKTIF KRONIK - Putrawan, Ida Bagus; Ngurah Rai, Ida Bagus (journal of internal medicine; Vol. 9, No. 2 Mei 2008)
Chronic obstructive pulmonary disease (COPD) is a preventable and treatable disease, characterized by airflow limitation that is not fully reversible. The airflow limitation is usually progressive and associated with an abnormal inflammatory response of the lung to noxious particle or gases. There is a chronic inflammation that leads to fixed narrowing of small airways and alveolar wall destruction (emphysema). This characterized by increased number of alveolar macrophages, neutrophils and cytotoxic T-lymphocytes, and the release of multiple inflammatory mediators. A high level of oxidative stress may amplify this inflammation. There is also increased elastolysis and evidence for involvement of several elastolytic enzymes, including serine proteases, cathepsins and matrix metalloproteinasses. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines recommend a stepwise approach to disease management, with bronchodilators being the mainstay of treatment. 2-Adrenergic agonists induce bronchodilatation through stimulation of 2-receptors, leading to an increase in cyclic adenosine monophosphate. In addition to prolonged bronchodilatation, long-acting 2-agonists (LABAs) exert other effects that may be of clinical relevance. These include inhibition of airway smooth-muscle cell proliferation and inflammatory mediator release, as well as nonsmooth-muscle effects, such as stimulation of mucociliary transport, cytoprotection of the respiratory mucosa, and attenuation of neutrophil recruitment and activation.
Keywords: COPD, long-acting 2-adrenergic agonists, salmeterol, formoterol